تأثير تكنولوجيا المعلومات على إدارة المعرفة دراسة مسحيّة في المركز الوطني للمتميّزين في جامعة تشرين - ديب كندة; زهرة فاتنة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى دراسة تأثير تكنولوجيا المعلومات على إدارة المعرفة في المركز الوطني للمتميّزين بجامعة تشرين، واعتمدت الباحثة على المنهج المقاربة الاستنباطيّة كمنهج عام للبحث، واتباع منهجيّة المسح، ولتحقيق أهداف البحث تم تطوير استبانة وتوزيعها على كافة رؤساء الأقسام والشّعب وكافة الموظفين الإداريّين والمدرسين في المركز الوطني للمتميّزين؛ حيث بلغ عددهم (116)، ثمّ أجريت عليها التّحليلات الإحصائيّة المناسبة، ومن أهمّ النّتائج الّتي تم التّوصّل إليها: امتلاك المركز الوطني للمتميّزين في جامعة تشرين تكنولوجيا معلومات قادرة على التأثير وتفعيل إدارة المعرفة في المركز، حيث أثبتت نتيجة الفرضيّة الرّئيسة وجود علاقة معنويّة ذات دلالة إحصائيّة بين تكنولوجيا المعلومات وإدارة المعرفة. وفي ضوء النّتائج الّتي توصّل إليها البحث تقترح الباحثة ما يلي: ضرورة تطوير وتحديث البنى التّحتيّة لتكنولوجيا المعلومات في المركز الوطني للمتميّزين في جامعة تشرين. The research aims to study the impact of information technology on knowledge management in National Center for the distinguished in Tishreen University. The researcher relied on the deductive approach as a general method. She follows a survey methodology. To achieve the objectives of the research, a questionnaire was developed and distributed for all heads of department in the center, and all administrative staff and teacher. Were (116) questionnaires, and the appropriate statistical analyzes were conducted. The most important results were: · The National Center for the distinguished have an information technology that capable in influencing and activating knowledge management in the center. Where the main hypothesis proved there is a statistically significant relationship between information technology and knowledge management. In light of the research finding, the researcher proposes the following: · The need to improve and development the information technology Infrastructure in the National Center for the distinguished.